Peripheral administration of neuropeptide W inhibits gastric emptying in rats: the role of small diameter afferent fibers and cholecystokinin receptors - YEGEN, BERRAK (My University, 2023)
Neuropeptide W (NPW), a novel hypothalamic peptide, contributes to the central regulation of food intake and energy balance, and suppresses feeding behavior when administered centrally. The aim of our study was to investigate the role of peripherally administered NPW in the modulation of gastric emptying, and to evaluate the participation of afferent fibers, cholecystokinin (CCK) receptors and gastric smooth muscle contractility in the regulatory effects of NPW on gastric motility. In Sprague-Dawley male rats equipped with gastric fistula, gastric emptying rate of the saline and peptone solutions was measured following subcutaneous administration of NPW (0.1 or 5 μg/kg) preceded by subcutaneous injections of saline, CCK-1 or CCK-2 receptor antagonists. Another group of rats with cannulas were injected subcutaneously with capsaicin for afferent denervation before commencing emptying trials. The effect of NPW on carbachol-induced gastric contractility and the role of CCK receptors in gastric smooth muscle contractility were also assessed in gastric strips. Peripheral injection of NPW delayed gastric emptying rate of both caloric and non-caloric liquid test meals, while administration of CCK-1 or CCK-2 receptor antagonists or denervation of small diameter afferents reversed NPW–induced delay in gastric emptying. Moreover, NPW inhibited antrum contractility in the organ bath. Our results revealed that peripherally administered NPW delayed liquid emptying from the stomach via the involvement of small diameter afferent neurons and CCK receptors, and thereby this regulatory role may contribute to its central regulatory role in controlling food intake and energy balance.
Keywords: Neuropeptide W; Gastric motility; Small diameter afferent nerves; Cholecystokinin receptors